Disability studies and the inclusive classroom critical practices for embracing diversity in education - Baglieri, Susan; Shapiro, Arthur (Routledge, 2017)
Disability Studies and the Inclusive Classroom is a core textbook that integrates knowledge and practice from the fields of disability studies and special education. The second edition has been fully revised and updated throughout to include stronger connections between race, class, sexual orientation, gender, and disability to emphasize intersecting identities and experiences; stronger emphasis on curriculum and teaching rather than on attitudes toward disability; and updates to current events, cultural references, resources, research literature, laws, and policies. -- Provided by publisher.